ASSESSMENT OF INTENSIVE CARE NURSES' PERCEPTIONS REGARDİNG OBESITY TAX - Derya Akça Doğan; Derya Bıçak Ayık (International Journal of Health Services Research and Policy)
Obesity has become an increasingly significant health issue affecting both individuals and societies, leading many countries to implement various strategies to address this threat. One of these strategies is the obesity tax, which is applied to foods with low nutritional value and high fat, sugar, and calorie content. Healthcare professionals, particularly intensive care nurses, face additional challenges when caring for obese patients during this process. This research aims to assess the perceptions of intensive care nurses regarding obesity taxation. The descriptive study involved 92 intensive care nurses. Data were collected using a form to determine nurses' demographic characteristics and the Obesity Tax Perception Scale. A significant 94.6% of the surveyed nurses reported challenges in providing care for obese individuals. Most participants indicated a perception of a high tax burden. The statement "The fight against obesity is one of the main tasks of the state" received the highest support on the scale (3.93±1.13). There was also a strong endorsement of the statement, "The fight against obesity should be through non-tax instruments" (3.77±0.89). Conversely, the statement "Taxes should be the primary tool in the fight against obesity" received the least support, registering a mean of 2.28±1.11 from the participants. The findings indicate that intensive care nurses believe in government intervention in fighting obesity; however, they prefer that this intervention occur through non-taxation measures. These results underscore the importance of considering the perspectives of healthcare professionals in shaping effective policies and strategies against obesity.